2016
DOI: 10.1080/00071668.2016.1192280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary conjugated linoleic acid affects blood parameters, liver morphology and expression of selected hepatic genes in laying hens

Abstract: The objective of this research were to investigate the effect of a conjugated linoleic acid (CLA)-enriched diet on Isa Brown laying hen health status and to provide a comprehensive analysis of changes in blood parameters, liver morphology and selected hepatic gene expression. Hens were allocated to the control and experimental group (diet enriched with 0.75% CLA) for a total period of 4 m. At the end of the experiment half of the hens from each group were slaughtered for analyses. The remaining hens were trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
0
16
0
4
Order By: Relevance
“…Supplemental Figure S3 shows the Q-Q plot for these interactions, indicating a good performance. The ME1 gene is located on chromosome 6 and it is a plausible candidate for gene-diet interactions, taking into account that this gene is involved in fatty acids synthesis in the liver [123,124] and its modulation by the dietary fat content has been reported [124,125]. Figure 6 shows the regional plot for the top-ranked SNPs, ME1-rs3798890 (p = 2.15 × 10 −7 ) in the genome-wide interaction analysis with Mediterranean diet.…”
Section: Gwas For Serum Omega-3 Pufa (%) In This Populationmentioning
confidence: 99%
“…Supplemental Figure S3 shows the Q-Q plot for these interactions, indicating a good performance. The ME1 gene is located on chromosome 6 and it is a plausible candidate for gene-diet interactions, taking into account that this gene is involved in fatty acids synthesis in the liver [123,124] and its modulation by the dietary fat content has been reported [124,125]. Figure 6 shows the regional plot for the top-ranked SNPs, ME1-rs3798890 (p = 2.15 × 10 −7 ) in the genome-wide interaction analysis with Mediterranean diet.…”
Section: Gwas For Serum Omega-3 Pufa (%) In This Populationmentioning
confidence: 99%
“…Available literature would support such a hypothesis as numerous studies showed an inhibitory effect, especially for cis9,trans11CLA isomer, on tumor cells [28–32]. Indeed, our analysis of FA profile of CLA-enriched egg yolk showed that cis9,trans11CLA was incorporated more efficiently (3 : 1 ratio) than trans10,cis12 isomer [21] and therefore could predominate in EFA-CLA. Interestingly, comparison of the effect of synthetic CLA isomers with CLA-EFA from egg yolk showed the advantage of the latter in reducing cancer cell viability (Figure 1).…”
Section: Discussionmentioning
confidence: 53%
“…Production of CLA-enriched egg yolks was performed in the National Research Institute of Animal Production in Krakow (Poland), as per the recommendations of the Local Animal Ethics Committee (approval number: 851/2011) as described previously [21]. Eggs were collected and stored at 4°C, and yolks were separated from albumen, homogenized, and frozen at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…As pro-inflammatory factors, IL-1, IL-6, and TNF-α have been used for evaluating infectious and inflammatory reaction-associated immunity in humans and various animals including chickens [52][53][54]. TNF-α plays an important role in the pathogenesis of mammals' NAFLD [55] and has a close relationship with the liver steatosis, fibrosis, and apoptosis [56,57].…”
Section: Discussionmentioning
confidence: 99%